Women in early Indian Buddhism : comparative textual studies (South Asia Research, 2014)
The path of practice as taught in ancient India by Gotama Buddha was open to both women and men. The texts of early Indian Buddhism show that women were lay followers of the Buddha and were also granted the right to ordain and become nuns. Certain women were known as influential teachers of men and women alike and considered experts in certain aspects of Gotama's dhamma. For this to occur in an ancient religion practiced within traditional societies is really quite extraordinary. This is apparent especially in light of the continued problems experienced by practitioners of many religions today involved in challenging instilled norms and practices and conferring the status of any high office upon women.